Railway Terminology As An Object Of Study In Linguistics (Eurasian Scientific Herald, 2025)
This article explores the study of railway terminology as an object of linguistic research, emphasizing the intersection of language, technology, and culture. It examines the role of international and national terms in the railway sector, highlighting the dominant influence of global terminology while acknowledging the importance of linguistic adaptation to local languages. The study investigates translation strategies such as transliteration, adaptation, and equivalence, which ensure both technical precision and cultural relevance in the transfer of railway terms across languages. The findings suggest that the ongoing evolution of railway terminology is influenced by technological advances, necessitating the continuous development of new terms. This research calls for interdisciplinary collaboration among linguists, engineers, and translators to standardize multilingual resources, improving communication and enhancing global understanding of railway systems.